2017
DOI: 10.31227/osf.io/6hsqr
|View full text |Cite
Preprint
|
Sign up to set email alerts
|

The Relevance of Marketing Mix and Service Quality on Students' Decision-Making Factors Regarding Higher Education and Satisfaction

Abstract: ABSTRACT

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

0
0
1

Year Published

2024
2024
2024
2024

Publication Types

Select...
1

Relationship

0
1

Authors

Journals

citations
Cited by 1 publication
(1 citation statement)
references
References 2 publications
0
0
1
Order By: Relevance
“…This means that the appearance and abilities of employees, lecturers and teaching staff do not greatly impact students' decision-making in choosing a university. This is contrary to previous research by Tijjang et al (2017), Saurombe et al (2017), and Riofita (2018), which found that informant resources have a large influence on decision-making. Students are more concerned with the reputation and legitimacy of the institution, which is evaluated based on achievements and accreditation rankings.…”
Section: The Influence Of Narcotics Resources On Student Decisionscontrasting
confidence: 99%
“…This means that the appearance and abilities of employees, lecturers and teaching staff do not greatly impact students' decision-making in choosing a university. This is contrary to previous research by Tijjang et al (2017), Saurombe et al (2017), and Riofita (2018), which found that informant resources have a large influence on decision-making. Students are more concerned with the reputation and legitimacy of the institution, which is evaluated based on achievements and accreditation rankings.…”
Section: The Influence Of Narcotics Resources On Student Decisionscontrasting
confidence: 99%